Development of the youth athlete - Armstrong, Neil (Routledge, Taylor & Francis Group, 2019)
The book offers an evidence-based, integrated analysis of the development and trainability of the morphological and physiological characteristics which influence sport performance in youth. The author critically analyses the development of the youth athlete in the context of current and future sport performance and long-term health and well-being, identifies the principal controversies in youth sport, and addresses them through sport- specific examples. The book focuses on the interactions between growth, maturation, and: sport-related fitness, sport-specific trainability, sport performance, and challenges in youth sport